Methods and results regarding sinusoid modulated pulse gas metal arc welding. Issue 5 (September 2016) - Wang, Leilei; Heng, Gongchun; Chen, Hui; Xue, Jiaxiang; Lin, Fanglue; Huang, Wenjin
Abstract In this investigation, a sinusoid modulated pulse gas metal arc welding (SP-GMAW) method based on a current waveform control method and on the welding mechanism of pulsed gas metal arc welding (P-GMAW) was proposed. This method achieved smooth control over the welding current. The process formulas were simplified. Then, the control parameters were discussed and optimized. Finally, three comparison experiments were conducted. The results indicated that the SP-GMAW method, as an improved double-pulsed gas metal arc welding (DP-GMAW) method, had the following features: The SP-GMAW minimized porosity rate and generated palpable weld ripples in contrast with the P-GMAW. The SP-GMAW produced the finest fusion zone grain, highest fusion zone microhardness, and highest tensile strength among three welding methods. The feasibility and superiority of the method for welding aluminum sheet were verified.